Building writing center assessments that matter - Schendel, Ellen, author; Macauley, William J., author; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
No less than other divisions of the college or university, contemporary writing centers find themselves within a galaxy of competing questions and demands that relate to assessment--questions and demands that usually embed priorities from outside the purview of the writing center itself. Writing centers are used to certain kinds of assessment, both quantitative and qualitative, but are often unprepared to address larger institutional or societal issues. In Building Writing Center Assessments that Matter, Schendel and Macauley start from the kinds of assessment strengths already in place in writing centers, and they build a framework that can help writing centers satisfy local needs and put them in useful dialogue with the larger needs of their institutions, while staying rooted in writing assessment theory. The authors begin from the position that tutoring writers is already an assessment activity, and that good assessment practice (rooted in the work of Adler-Kassner, O'Neill, Moore, and Huot) already reflects the values of writing center theory and practice. They offer examples of assessments developed in local contexts, and of how assessment data built within those contexts can powerfully inform decisions and shape the futures of local writing centers. With additional contributions by Neal Lerner, Brian Huot and Nicole Caswell, and with a strong commitment to honoring on-site local needs, the volume does not advocate a one-size-fits-all answer. But, like the modeling often used in a writing consultation, examples here illustrate how important assessment principles have been applied in a range of local contexts. Ultimately, Building Writing Assessments that Matter describes a theory stance toward assessment for writing centers that honors the uniqueness of the writing center context, and examples of assessment in action that are concrete, manageable, portable, and adaptable.--Provided by publisher.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- United States; Writing centers -- United States